2019
DOI: 10.1155/2019/9051929
|View full text |Cite
|
Sign up to set email alerts
|

Association of Tumor Necrosis Factor Alpha, Interleukin 6, and C-Reactive Protein with the Risk of Developing Type 2 Diabetes: A Retrospective Cohort Study of Rural Thais

Abstract: The linkage of obesity, inflammation, and type 2 diabetes mellitus (T2DM) has been extensively investigated for over a decade. However, the association between inflammatory biomarkers, including C-reactive protein (CRP), interleukin 6 (IL-6), and tumor necrosis factor alpha (TNF-α), and T2DM is still inconsistent and limited. Thus, this study is aimed at elucidating the association between inflammatory marker levels and the risk of developing T2DM in many aspects. Among 296 subjects enrolled in 2013, 248 non-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 42 publications
(50 reference statements)
2
41
0
1
Order By: Relevance
“…Several studies focused their attention on the role of inflammation in the pathogenesis of DM. In particular, many authors demonstrated that elevated levels of C-reactive protein (CRP), IL-6, TNF-α predict the development of T2DM [4][5][6][7][8][9]. Hotamisligil and colleagues found that levels of TNF-α are elevated in the adipose tissue of obese insulin-resistant rodents and obese humans, and that the neutralization of TNF-α in insulin-resistant rodents resulted in an increase peripheral uptake of glucose in response to insulin [10,11].…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Several studies focused their attention on the role of inflammation in the pathogenesis of DM. In particular, many authors demonstrated that elevated levels of C-reactive protein (CRP), IL-6, TNF-α predict the development of T2DM [4][5][6][7][8][9]. Hotamisligil and colleagues found that levels of TNF-α are elevated in the adipose tissue of obese insulin-resistant rodents and obese humans, and that the neutralization of TNF-α in insulin-resistant rodents resulted in an increase peripheral uptake of glucose in response to insulin [10,11].…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…TNF-α is a pro-inflammatory, cell signaling protein that plays critical roles in inflammatory and autoimmune responses, cellular events such as apoptosis and cell differentiation, and oxidative stress. [88][89][90] Elevated concentrations of TNF-α are associated with insulin resistance, making it a contributory biomarker of type 2 diabetes. [88][89][90][91] TNF-α works to reduce the expression of glucose transporter type 4 (GLUT-4) and serine phosphorylation of insulin receptor substrate 1 (IRS-1), both of which are critical for the synthesis of insulin.…”
Section: C-reactive Protein (Crp)mentioning
confidence: 99%
“…[88][89][90] Elevated concentrations of TNF-α are associated with insulin resistance, making it a contributory biomarker of type 2 diabetes. [88][89][90][91] TNF-α works to reduce the expression of glucose transporter type 4 (GLUT-4) and serine phosphorylation of insulin receptor substrate 1 (IRS-1), both of which are critical for the synthesis of insulin. [92][93][94] TNF-α activates the endothelial production of adhesion molecules such as intracellular adhesion molecule-1.…”
Section: C-reactive Protein (Crp)mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Previous investigations have broadly revealed the relationship of high C-reactive protein (CRP) levels with IR and progression of T2DM (Phosat et al 2017). While interleukine (IL)-6 plays an exceptional role in the development of T2DM and elevated TNF-α levels over time could be a potential predictor of T2DM over time (Lainampetch et al 2019). In addition to cytokines released in response to several stimuli and immune system dysregulation (Banerjee and Saxena 2012), adaptor proteins are another type, which is a very important constituent of signaling transduction systems both beyond and within the immune system (Verma et al 2020).…”
Section: Introductionmentioning
confidence: 99%